Seasonal study of stable carbon and nitrogen isotopic composition in fine aerosols at a Central European rural background station - P. Vodička; P. Vodička; K. Kawamura; J. Schwarz; B. Kunwar; V. Ždímal (Atmospheric Chemistry and Physics, 2019)
A study of the stable carbon isotope ratios (δ13C) of total carbon (TC) and the nitrogen isotope ratios (δ15N) of total nitrogen (TN) was carried out for fine aerosol particles (PM1) and was undertaken every 2 days with a 24 h sampling period at a rural background site in Košetice (Central Europe) from 27 September 2013 to 9 August 2014 (n=146). We found a seasonal pattern for both δ13C and δ15N. The seasonal variation in δ15N was characterized by lower values (average of 13.1±4.5 ‰) in winter and higher values (25.0±1.6 ‰) in summer. Autumn and spring were transition periods when the isotopic composition gradually changed due to the changing sources and ambient temperature. The seasonal variation in δ13C was less pronounced but more depleted in 13C in summer (-27.8±0.4<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="e3b07b92bcdb01cfe5a8c2c470d9babd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00001.svg" width="58pt" height="10pt" src="acp-19-3463-2019-ie00001.png"/></svg:svg> ‰) as compared to winter (-26.7±0.5<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="2025e72aedee8470a65076b55beca847"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00002.svg" width="58pt" height="10pt" src="acp-19-3463-2019-ie00002.png"/></svg:svg> ‰). A comparative analysis with water-soluble ions, organic carbon, elemental carbon, trace gases and meteorological parameters (mainly ambient temperature) has shown major associations with the isotopic compositions, which has provided greater knowledge and understanding of the corresponding processes. A comparison of δ15N with <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="ecc3e6dd5af0ffb1da8bfbfcb16b8e8b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00003.svg" width="25pt" height="16pt" src="acp-19-3463-2019-ie00003.png"/></svg:svg>, <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="97c709e7ff43e05afce356dc3f53b497"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00004.svg" width="24pt" height="15pt" src="acp-19-3463-2019-ie00004.png"/></svg:svg> and organic nitrogen (OrgN) revealed that although a higher content of <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="822fcc3376206f5298bc14405cca7022"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00005.svg" width="25pt" height="16pt" src="acp-19-3463-2019-ie00005.png"/></svg:svg> was associated with a decrease in the δ15N of TN, <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="b054521cc8a5d2267742c16e315b1d01"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00006.svg" width="24pt" height="15pt" src="acp-19-3463-2019-ie00006.png"/></svg:svg> and OrgN caused increases. The highest concentrations of nitrate, mainly represented by NH4NO3 related to the emissions from biomass burning leading to an average δ15N of TN (13.3 ‰) in winter. During spring, the percentage of <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="23164037a5a41a281ec2bd2a6e11aeb2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00007.svg" width="25pt" height="16pt" src="acp-19-3463-2019-ie00007.png"/></svg:svg> in PM1 decreased. An enrichment of 15N was probably driven by the equilibrium exchange between the gas and aerosol phases (NH3(g) ↔ <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0ee21626c7ea7176080e9ce12af1c86d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00008.svg" width="24pt" height="15pt" src="acp-19-3463-2019-ie00008.png"/></svg:svg>(p)), which is supported by the increased ambient temperature. This equilibrium was suppressed in early summer when the molar ratios of <msubsup>NH4+</msubsup>/<msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="ae696540f6947feedb28dca18d4713d1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-3463-2019-ie00009.svg" width="57pt" height="17pt" src="acp-19-3463-2019-ie00009.png"/></svg:svg> reached 2, and the nitrate partitioning in aerosol was negligible due to the increased ambient temperature. Summertime δ15N values were among the highest, suggesting the aging of ammonium sulfate and OrgN aerosols. Such aged aerosols can be coated by organics in which 13C enrichment takes place by the photooxidation process. This result was supported by a positive correlation of δ13C with ambient temperature and ozone, as observed in the summer season. During winter, we observed an event with the lowest δ15N and highest δ13C values. The winter event occurred in prevailing southeast air masses. Although the higher δ13C values probably originated from biomass-burning particles, the lowest δ15N values were probably associated with agriculture emissions of NH3 under low-temperature conditions (< 0 ∘C).